(untitled) (PerCursos, 2024)
In this paper, we examine Antonio Gramsci’s contributions in working-class education, to which he always given extreme importance. We also highlight his prolific theoretical production as an expression of historical materialism, which is essential to understand his intense intellectual activity on a variety of matters. This essay gives special focus on education and, to do so, refers to his pre-prison political writings, linking them to the fundamental contributions of Prison Notebook 12. The selected works highlight the indispensability of education for the working-class and the call, to this class, to be a protagonist in its own education. We also address the author strong criticism of the ruling class biased perspective in the working-class education and his warning about the importance of a solid and active, cultural and political preparation articulated by the organic intellectuals of this class. The philosopher’s contributions are discussed without focusing on the pre-prison/prison dichotomy, but in search of his intellectual journeymeaning, regarding the overcoming of the current order and the establishment of the socialist alternative, which necessarily takes place through the class struggle. In this way, we attempt to show that in his contribution to the working-class education he always considered it to be amaterial base expression and aimed to overcome class society. We also underline Gramsci’s emphasis on the need for workers’ education to make them capable of govern and control those who are governing, both in order to win the class struggle and to keep the continuity of this victory through the historical process.